Optimizing process conditions for improved Hf1−xZrxO2 ferroelectric capacitor performance - Mittmann, Terence; Fengler, Franz P.G.; Richter, Claudia; Park, Min Hyuk; Mikolajick, Thomas; Schroeder, Uwe (Microelectronic engineering, 2017)
The recently reported ferroelectric phase in doped hafnium oxide films enabled various devices ranging from non-volatile applications to negative capacitance field effect transistors. This study analyses the structural and electrical changes in ferroelectric Hf1−xZrxO2 based metal-insulator-metal capacitors. Planar metal-ferroelectric-metal stacks of different composition, thickness and purge times were prepared by atomic layer deposition for the Hf1−xZrxO2 films with metal organic precursors, water as oxygen source and reactive physical vapor deposition of TiN electrodes. With the optimization of the process route it was possible to improve the endurance and the remanent polarization of the ferroelectric capacitor. The analysis proved that the reduction of the impurities in the film is decreasing the non-ferroelectric monoclinic phase fraction with increasing purge time. An increase of the annealing temperature from 500 to 800°C resulted in a higher amount of the ferroelectric orthorhombic phase fraction, but also caused a reduced endurance. Impedance spectroscopy indicated the existence of an interfacial dead layer and its widening with higher anneal temperatures. [Display omitted] •Atomic layer deposition and anneal conditions were improved to optimize the Hf1−xZrxO2 ferroelectric capacitor performance.•Dielectric relaxation and impedance spectroscopy measurements have been performed to study the TiN/Hf1−xZrxO2-interface.•Hf1−xZrxO2 film thicknesses in the range of 10 to 15nm are favorable for the ferroelectric orthorhombic phase.•High anneal temperatures increases remanent polarization and reduces the wake up but decreases the endurance.•The thickness of the TiN/Hf1−xZrxO2-interface is increasing with increasing anneal temperature.